Precise Tuning of Skyrmion Density in a Controllable Manner by Ion Irradiation - Hu, Yue; Zhang, Senfu; Zhu, Yingmei; Song, Chengkun; Huang, Junfeng; Liu, Chen; Meng, Xuan; Deng, Xia; Zhu, Liu; Guan, Chaoshuai; Yang, Hongxin; Si, Mingsu; et al. (ACS applied materials & interfaces, 2022)
Magnetic skyrmions are topologically protected spin textures that were found to be promising candidates for next-generation spintronic devices owing to their small size and unique current-induced dynamics. Increasing skyrmions density at designated locations in a controllable manner is a prerequisite to further improve the recording density of magnetic memory devices and relevant spintronics. Here, we demonstrate that a sharp increase in skyrmion density in magnetic multilayer films can be purposefully realized at a site-specific position by ion irradiation, which has industrial applicability. The Cs-scanning transmission electron microscopy and micromagnetic simulation results indicate that the skyrmions density can be sharply increased five times after applying an exposure with an irradiation dose of 1.5 × 1014 Ga+/cm2, and the magnetic field required to create skyrmions is also reduced. The intrinsic physical mechanism of increasing skyrmion density is found to mainly originate from the formation of disorders through Ga+ irradiation, which can induce a decrease in the nucleation energy barrier of skyrmions. We further show that the artificial skyrmion patterns with tunable density can be intentionally written at specific sites by using a Ga+ ion beam. This work should contribute a significant step toward eventually realizing the practical recording application of magnetic skyrmions.